EFFECTS OF PERMANENT AND TRANSITORY TAX CHANGES IN A LIFE‐CYCLE LABOR SUPPLY MODEL WITH HUMAN CAPITAL. (May 2015) - Keane, Michael P.
<x xml:space="preserve">Abstract</x> I examine effects of labor income taxation in life‐cycle models with human capital accumulation. In this case, the opportunity cost of time equals the wage plus returns to work experience. This has several interesting consequences: First, the data appear consistent with larger labor supply elasticities than prior work suggests. Second, contrary to conventional wisdom, permanent tax changes can have larger effects on current labor supply than temporary changes. Third, human capital dampens responses of young workers to transitory tax changes. Fourth, labor supply elasticities increase with age. Fifth, human capital amplifies the effect of permanent tax changes in the long run.